Report on the Phytoplankton Pigments measured during the JARE-31 Cruise to Syowa Station, Antarctica, November 1989 to March 1990 - Konno, Toshinori; Suzuki, Toshikazu; Fukuchi, Mitsuo (National Institute of Polar Research, 1996)
P(論文) departmental bulletin paper